Analisis Peran Tutor Sebaya Terhadap Motivasi Menghafal Al-Qur’an Mahasantri Putri Ma’had Al-Jami’ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu - Winda Widianingrum; Nasron; Rossi Delta Fitrianah (JPT : Jurnal Pendidikan Tematik, 2024)
The purpose of this study is to determine the role of peer tutors on the motivation of memorizing the Qur'an for students and describe the supporting and inhibiting factors / obstacles for students in memorizing the Qur'an. The method used by the researcher in this research is a qualitative research method using a qualitative descriptive approach. Data collection techniques were carried out by observation, interviews, and documentation using data analysis techniques, namely data reduction, data presentation, and conclusion drawing/verification. The results showed that the role of peer tutors on the motivation of memorizing the Qur'an of students had a positive impact. With peer tutors in each room, it will make it easier for mahsantri to deposit memorization, tahsin, and become a place to ask questions and learn. Although the students when memorizing the Qur'an have inhibiting factors that exist from within the students, namely internal factors, namely a sense of laziness and from outside the students, namely external factors, namely many assignments from campus and other activities in Ma'had besides memorizing the Qur'an. an. However, all inhibiting factors can be tolerated by supporting factors, namely the desire to become a hafizh of the Qur'an, support from family, ustadz/ustadzah, comrades in arms, and peer tutors who always motivate the spirit of memorizing the Qur'an.